Inverse optimality of pure proportional navigation guidance for stationary targets - Lee, Seokwon; Cho, Namhoon (AIAA, 2021)
The main contribution of this study is the optimality analysis of the PPNG performed in full generality. The new theoretical findings can explain the result of the former analysis in which the PPNG is derived as the minimum effort solution [5] and also describe a comprehensive design framework including the observability-enhanced guidance laws developed for the dual homing guidance problem. Furthermore, this study provides several examples illustrating how the PPNG with various navigation gain functions can be understood as optimal control solutions.